Software Development For Energy Audit Practice - Sariman, Muhammad Ehsan (UTeM, 2009)
This paper presents the development of software to audit the energy usage on the lighting system, air-conditioning system, and motor machine system. This software will be developed by using Microsoft Visual Basic as a programming language. Basic development of this software is using knowledge base (database), inference engine (decision), graphical user interface (GUI), user and output (energy audits report). The main purpose of this software is to help users to identify their daily energy usage to solve the wastage energy usage problem. This software can be applied to seven type of commercial building according to the tariff provided. Software will calculate the energy usage according to the type of system, number of item, and the total hour used. This software also can apply in the new installation of the systems. Software also will calculate cost for the energy usage depends on the tariff and type of equipment used. Final stage of this software will show the result of the energy audits. The result shows total amount of energy usage in kWh/day, kWh/month and total energy cost per month in RM. The last audit report in this software can be print as a layout.